Potencial de regeneração natural e crescimento de Millettia stuhlmannii Taub. em floresta de miombo como subsídio para o manejo sustentável - Hofiço, Noé dos Santos Ananias (2021)
Millettia stuhlmannii Taub. (Fabaceae) is a highly desirable tropical timber species across its range in Southeast Africa and one of the three most important timber trees in Mozambique, where it is heavily exploited. Despite its importance, little is known about natural regeneration, its spatial distribution patterns and growth rates, which are fundamental to establishing economic strategies and management and conservation policies. This study aimed to evaluate autecological aspects of M. stuhlmannii regeneration, spatial patterns and growth rates in the Miombo forest with different types of land use in Cheringoma and Muanza Districts, in Mozambique. Four specific land uses were selected, (i) undisturbed forest; (ii) selective logging forest; (iii) slash & burn agriculture; and (iv) frequent fire. A census was carried out for regeneration in each land use, measuring the variables diameter at 10 cm from the ground, total height, and geographic coordinates obtained. Density and forms of origin of regeneration were determined in the profile of the diameter and height classes among the different land uses. The hypothesis of complete spatial randomness (CSR) of regeneration was tested by constructing confidence envelopes for the correlation function par g (r), using a homogeneous Poisson process. Growth data obtained from 50 M. stuhlmannii trees distributed in different diameter classes were used, covering individuals with DBH from 10 cm to 60 cm. Samples were taken from cross sections of each tree at 1.3 m from the ground. Growth rings were counted and measured in four radii of each disc and radial increment rates were estimated through ring widths. The results showed that M. stuhlmannii regenerates through the seed, from the stump and roots. The forms of origin of regeneration and the levels of recruitment vary according to the type of land use. M. stuhlmannii is a light-demanding species and requires maximum exposure to sunlight to grow rapidly, but regeneration takes place more readily to the exclusion of fire. The main spatial patterns of regeneration showed a tendency to aggregate at very close distances between the origin forms of M. stuhlmannii and the types of land use. The trees of M. stuhlmannii were 40 to 49 years old, in the undisturbed forest and in the selective logging area, with average annual growth in diameter at 1.3 m from the ground ranging from 6.52 to 6.54 mm and in the area of agricultural cultivation and frequent fire, 50 to 58 years, with average annual growth in diameter ranging from 5.69 to 5.75 mm. The results indicate that the average time for M. stuhlmannii to pass from one 10 cm class to another was estimated at 22 years and to reach 40 cm diameter was estimated at, on average, 66 years, which corresponds to the cutting cycle. These results provide a useful baseline for the development of sustainable management plans for M. stuhlmannii and restoration and conservation strategies, as well as for other economically exploited timber species in Mozambique.